EFEK PEMBERIAN GLUKOMANAN UMBI PORANG (Amorphophallus oncophyllus Prain ex Hook. f.) TERHADAP KADAR KOLESTEROL TOTAL DARAH TIKUS YANG DIBERI DIET TINGGI LEMAK - Bekti Nugraheni; Intan Martha Cahyani; Kyky Herlyanti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACTIndonesia is a country with abundant natural resources, one of which tubers. Plants types of tubers that have a lot of glucomannan content of the tuber porang. Glucomannan is used as a diet in patients with hypercholesterolemia. Glucomannan from tubers porang (Amorphophallus oncophyllus Prain ex Hook.f.) serves as a water-soluble fiber and have a low calorie.The purpose of this study was to determine the effect of glucomannan tuber porang (Amorphophallus oncophyllus Prain ex Hook.f.) to decrease total blood cholesterol mice fed a high-fat diet and to determine what dose of glucomannan tubers porang most effective for lowering blood cholesterol.The treatment in this study is glucomannan flour dose of 25 mg / kg; 50 mg / kg; and 100 mg / kg. The population in this study was a white rat (Rattus norvegicus) males aged 2-3 months with BB ± 200 g.Giving glucomannan porang tubers dose 25 mg / kg; 50 mg / kg; and 100 mg / kg give effect to the reduction in total blood cholesterol mice fed a high-fat diet. Effective dose for lowering total cholesterol levels of mice that is 50 mg / kg.Keywords: glucomannan tuber porang (Amorphophallus oncophyllus Prain ex Hook.f.), total cholesterol.